The complete mitogenome of the hermit crab Clibanarius infraspinatus (Hilgendorf, 1869), (Crustacea; Decapoda; Diogenidae) – a new gene order for the Decapoda. (1st November 2016) - Gan, Huan You; Gan, Han Ming; Tan, Mun Hua; Lee, Yin Peng; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the hermit crab Clibanarius infraspinatus was recovered by genome skimming using Next-Gen sequencing. The Clibanarius infraspinatus mitogenome has 16, 504 base pairs (67.94% A + T content) made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs and a putative 1500 bp non-coding AT-rich region. The Clibanarius infraspinatus mitogenome sequence is the first for the family Diogenidae and the second for the superfamily Paguroidea and exhibits a translocation of the ND3 gene not previously reported for the Decapoda.